xy(x + 1)(x + 2)
(x-y) + (xy - 1) = (x - 1)(y + 1)
If that's xy + x^2y, it factors to xy(x + 1) If it's something else, please re-submit your question with any plus signs written out.
xy + x + y + 1 is an expression, not an equation. An expression cannot be solved.
x+xy=8 xy=-x+8 y=-1+8/x
2x squared plus 2x plus xy plus y or 2x(x+1) + y(x+1) or (x+1)(2x+y)
(x + 2)(y + 1)
I understand you want [(2/x) + (1/y)] as a single fraction. The common denominator is (xy): 2/x = (2y)/(xy); and 1/y = x/(xy), so the answer is (2y + x) / (xy)
Divide by 'x'; x2+xy/x = x(x+y)